ANTI-TNF THERAPY PERSPECTIVES IN RHEUMATOLOGIC PRACTICE - E.I. Alexeeva; T.М. Bzarova; S.I. Valieva; A.M. Alekseeva; A.M. Chomakhidze; K.B. Isaeva; E.G. Chistyakova; R.V. Denisova ("Paediatrician" Publishers LLC, 2008)
The overview is dedicated to the application of anti TNF medication to treat rheumatoid diseases among adults and children. The researchers provided for the data on the individual, open and multicentered, double, blind, placebobcontrolled research of infliximab, etanercept, adalimumab efficacy. The research findings witnessed high efficacy and safety of anti TNF therapy in both adult and children rheumatologic practice.Key words: infliximab, etanercept, adalimumab, children, treatment, juvenile rheumatoid arthritis, rheumatoid arthritis.